'Belonging Means you can Go In': Children's Perspectives and Experiences of Membership of Kindergarten. Issue 1 (March 2014) - Joerdens, Sarah Heinrich
STARTING FORMAL SCHOOLING IS a significant transition for young children and their families; a process rather than a one-off event. A sense of belonging or membership is identified by key national documents in early learning as critical to young children's wellbeing and as an essential aspect of quality care and education (DEEWR, 2009, 2010). This paper provides an overview of a partial ethnography conducted over one year with children in their first year of formal school (known as Kindergarten in the site under study). The study investigated young children's experiences and perspectives during their first year of school. The results of the study indicate that children become members of the group or community of practice (CoP) (Wenger, 1998) as they begin school and their membership emerges as they participate in this CoP. Data from the study documents and celebrates young children's competencies in negotiating and participating in their Kindergarten CoP and becoming members of the school.